Linking Physical and Mental Health Summary Scores from the Veterans RAND 12-Item Health Survey (VR-12) to the PROMIS(®) Global Health Scale - Schalet, Benjamin D. (J Gen Intern Med, 2015)
BACKGROUND: Global health measures represent an attractive option for researchers and clinicians seeking a brief snapshot of a patient’s overall perspective on his or her health. Because scores on different global health measures are not comparable, comparative effectiveness research (CER) is challenging. OBJECTIVE: To establish a common reporting metric so that the physical and mental health scores on the Veterans RAND 12-Item Health Survey (VR-12(©)) can be converted into scores on the corresponding Patient Reported Outcomes Measurement Information System (PROMIS(®)) Global Health scores. DESIGN: Following a single-sample linking design, participants from an Internet panel completed items from the PROMIS Global Health and VR-12 Health Survey. A common metric was created using analyses based on item response theory (IRT), producing score cross-walk tables for the mental and physical health components of each measure. The linking relationships were evaluated by calculating the standard deviation of differences between the observed and linked PROMIS scores and estimating confidence intervals by sample size. PARTICIPANTS: Participants (N = 2025) were 49 % male and 73 % white; mean age was 46 years. MAIN MEASURES: Mental and physical health subscales of the PROMIS Global Health and the VR-12. The mean VR-12 physical component and mental component scores were 45.2 and 46.6, respectively; the mean PROMIS physical and mental health scores were 48.3 and 48.5, respectively. KEY RESULTS: We found evidence that the combined set of VR-12 and PROMIS items were relatively unidimensional and that we could proceed with linking. Linking worked better between the physical health than mental health scores using VR-12 item responses (vs. linking based on algorithmic scores). For each of the cross-walks, users can minimize the impact of linking error with modest increases in sample sizes. CONCLUSIONS: VR-12 scores can be expressed on the PROMIS Global Health metric to facilitate the evaluation of treatment, including CER. Extending these results to other common measures of global health is encouraged. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-015-3453-9) contains supplementary material, which is available to authorized users.